Educação musical, jovens e pesquisa na internet: Compartilhando procedimentos metodológicos - Arroyo, Margarete [UNESP]; Bechara, Silvia Regina C. C. [UNESP]; Paarmann, Heraldo [UNESP] (OPUS, 2017)
This article shares and discusses methodological procedures that used the internet as a tool and an empirical field of research for learning music by Brazilian youth and adolescents. With reference to three studies involving digital natives, the purpose of this article is to stress the importance of the internet as a context and instigator for contemporary research in the area of music education. The three qualitative studies performed data collection between January 2011 and April 2015 and used online research methods such as documentary research on the internet, virtual ethnography and multiple on-line case studies. In addition to the possibilities that these three studies performed on and with the internet indicated, further research is deemed plausible such as longitudinal and comparative studies.
Music education, youth and research on the internet: Sharing methodological procedures
Keywords: Music education; Research on the internet.; Youth